ANALISIS GEOSPASIAL PRODUKSI BERAS TERHADAP KEBUTUHAN MASYARAKAT MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS DI KABUPATEN BANJAR PROPINSI KALIMANTAN SELATAN - Sari, Dewi Nur Indah; Sobatnu, Ferry; Batara, Yastin David (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2020)
Production of agricultural products will depend on the area of ​​land used as land for farming. If the area of ​​agricultural land shrinks, the productivity of the land will be low, and conversely if the area of ​​agricultural land is expanded then the productivity of the land will increase. Banjar District, South Kalimantan Province is known as one of the rice producers and suppliers for most of the South Kalimantan region, even its agricultural products are also sent to meet the rice needs of other regions such as Central Kalimantan, East Kalimantan, and some areas in Java. This study aims to calculate the deviation between rice production with rice needs for the population regarding to rice production factors, and then apply geospatial analysis for calculation results in each district administration area using Geographical Information System. The results showed that Banjar in 2016 had rice production surplus 85,847.2 ton and in 2017 also had rice production surplus 69151.74 ton. This result shows that in 2016 and 2017 Banjar still fulfill the riceneeds for the population. However, after analyze in each sub-district, there are sub-district that has low rice production compare to the. This is influenced by several factors including the increase in population and the reduction in the area of ​​land planted with rice commodities in Banjar. This creates a lack of equal distribution of rice production in the sub-districts in Banjar